Lack, excess, and time in the Cannibalist Manifesto by Oswald de Andrade - Ricardo Merlo, Hugo (História da Historiografia: International Journal of Theory and History of Historiography, 2024)
This article constitutes an endeavor to explore the relationship between figurations of lack and excess and historical time, particularly within the context of the manifold modernist temporalities in Brazil. We undertake this endeavor through a close reading of Oswald de Andrade’s Cannibalist Manifesto (1928), aiming to elucidate how the author employs notions of lack and excess to interrogate modern historical time as a device for synchronizing diverse temporalities. In conclusion, we underscore the significance of investigating artifacts of historical expression beyond conventional historiography, in order to grasp temporal experiences akin to those of Brazilian modernism, as well as to seek alternative modes of conveying the constituent multiplicity of the entire temporal experience.